2023
DOI: 10.3389/fnins.2023.1251968
|View full text |Cite
|
Sign up to set email alerts
|

Domain knowledge-assisted multi-objective evolutionary algorithm for channel selection in brain-computer interface systems

Tianyu Liu,
An Ye

Abstract: BackgroundFor non-invasive brain-computer interface systems (BCIs) with multiple electroencephalogram (EEG) channels, the key factor limiting their convenient application in the real world is how to perform reasonable channel selection while ensuring task accuracy, which can be modeled as a multi-objective optimization problem. Therefore, this paper proposed a two-objective problem model for the channel selection problem and introduced a domain knowledge-assisted multi-objective optimization algorithm (DK-MOEA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…Recently, there has been a rising trend in utilizing the correlation matrix of channels to address channel selection optimization problems. This is primarily because the correlation matrix can depict the interactions and cooperative activities among different brain regions (Liu and Ye, 2023 ). It has been demonstrated that due to the non-uniform connectivity patterns in the brain, the correlation matrix of EEG signals is typically sparse (Liu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been a rising trend in utilizing the correlation matrix of channels to address channel selection optimization problems. This is primarily because the correlation matrix can depict the interactions and cooperative activities among different brain regions (Liu and Ye, 2023 ). It has been demonstrated that due to the non-uniform connectivity patterns in the brain, the correlation matrix of EEG signals is typically sparse (Liu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%